Pharmacokinetics of Ceftazidime/Avibactam Following Intravenous Administration in Rabbits: Developing the Preclinical Foundation for Treatment of KPC-Kp Pneumonia in Immunocompromised Patients. (4th October 2017) - Petraitis, Vidmantas; Petraitiene, Ruta; Satlin, Michael; Maung, Bo Bo Win; Khan, Farehin; Mazur, Chase; Georgiades, Benjamin; Hayden, Joshua A; Walsh, Thomas J
Abstract: Background: CRE have been identified by the CDC as one of three urgent antibiotic resistance threats. The international emergence of these pathogens has largely been driven by the dissemination of carbapenemase-producing Klebsiella pneumoniae (KPC- Kp ), through enzymes that hydrolyze carbapenems and all other β-lactam agents. Ceftazidime/avibactam (CAZ-AVB) represents a promising alternative for the treatment of KPC- Kp pneumonia and bacteremia. However, little is known about the efficacy of CAZ-AVB in immunocompromised hosts. We therefore studied its plasma pharmacokinetics in order to establish humanized dosages for preclinical investigation of CAZ-AVB in treatment of KPC- Kp pneumonia. Methods: Three groups of four NZW rabbits received a single dose of ceftazidime/avibactam at 60, 90, and 120 mg/kg as an IV infusion. During the second stage, ceftazidime/avibactam was administered Q8h for 6 days with serial plasma sampling on day 7. Pharmacokinetic parameters were estimated using non-compartmental methods. Results: Single dose Multi-dose Conclusion: This study demonstrates that CAZ-AVB displays linear dose proportional exposures simulating those of human plasma pharmacokinetics profiles and further establishes the preclinical foundation for treatment of immunocompromised patients. Disclosures: M. Satlin, Hardy Diagnostics: Investigator, Research support. Allergan: Grant Investigator, Research grant. Merck: Grant Investigator, Grant recipient. B. Georgiades, Allergan: Employee, Salary. T. J. Walsh, Astellas, Actavis, Contrafect, Drais, iCo, Novartis, Methylgene, Pfizer, Sigma-Tau: Consultant, Consulting fee. Astellas, Actavis, Merck, Novartis, Phizer, Sctnexis, Tetraphase, The Medicines Company, Theravance: Grant Investigator, Research grant.